Delving into Uncontrolled or Severe Asthma: Perspectives from Patients and Healthcare Professionals in a Cross-Sectional Study - Volpato E; Pennisi V; Pennisi A; Piraino A; Banfi PI; D'Antonio S; Centanni S; Cavalieri L; Ramaccia M; Bugliaro F; Barbaglia S; Cappuccio A; et al. (Journal of Asthma and Allergy)
Eleonora Volpato,1,2,* Vincenzo Pennisi,3,* Alfio Pennisi,3 Alessio Piraino,4 Paolo I Banfi,2 Salvatore D’Antonio,5 Stefano Centanni,6 Luca Cavalieri,7 Mattia Ramaccia,7 Filomena Bugliaro,8 Simona Barbaglia,9 Antonietta Cappuccio,10 Roberta Termini,10 Maria Giulia Marini10 1Dipartimento di Psicologia, Università Cattolica del Sacro Cuore, Milan, Italy; 2IRCCS Fondazione Don Carlo Gnocchi, Milan, Italy; 3Centro di riabilitazione Mons. Giosuè Calaciura, Biancavilla, Catania, Italy; 4Chiesi Farmaceutici S.p.A, Parma, Italy; 5Associazione Pazienti BPCO e altre patologie respiratorie, Rome, Italy; 6ASST- Santi Paolo e Carlo - Università degli Studi di Milano, Milan, Italy; 7Chiesi Italia S.p.A, Parma, Italy; 8Federasma e Allergie OdV - Federazione Italiana Pazienti, Prato, Italy; 9Associazione Nazionale Pazienti RESPIRIAMO INSIEME-APS, Padua, Italy; 10Healthcare Area, ISTUD, Milan, Italy*These authors contributed equally to this workCorrespondence: Eleonora Volpato, Department of Psychology, Università Cattolica del Sacro Cuore, Via Nirone, 15, Milan, CAP 20123, Italy, Tel +393293872692, Email eleonora.volpato@unicatt.itBackground: Despite the effectiveness of inhalation therapy, uncontrolled or severe asthma remains prevalent challenges in respiratory care Narrative Medicine (NM) offers a linguistic approach to comprehending illness experiences, thereby providing a framework for advancing healthcare.Aim: The primary aim of this study was to gather narratives from individuals grappling with severe or uncontrolled asthma and their Healthcare Professionals (HCPs), in order to explore the intricate interplay among quality of care, quality of life, psychological and social determinants, and adherence patterns.Methods: A cross-sectional NM study was conducted in Italy from February to December 2023, encompassing 135 patients with uncontrolled or severe asthma (54.7% male; mean age: 56.7 years) and 47 HCPs (64.9% male; mean age: 54.3 years). A mixed-method approach was adopted to scrutinize themes, language nuances, emotional expressions, and narrative classifications.Results: Patients with uncontrolled or severe asthma reported an average illness duration of 4.46 years, with exacerbations occurring over the past 20.9 months. Pulmonologists (83% of HCPs) played a predominant role in diagnosing and treating the disease in 96.1% of patients. Additionally, participants with severe asthma reported higher healthcare needs. The most reported emotions were fatigue (25.96%) and a sense of suffocation (11.53%). Upon commencing treatment, while experiencing physical improvement, patients predominantly expressed feelings of “submission/dependence” on medication (28%), followed by “fear” (21%) and “serenity/joy” (21%). HCPs, primarily pulmonologists (83%), emphasized the importance of raising awareness among specialists and General Practitioners (GPs), disseminating information, optimizing prescriptions, implementing phenotyping, tailoring therapy, and considering paediatric needs.Conclusion: These findings contribute to a deeper understanding of patient perspectives, facilitate personalized interventions, and underscore the factors influencing therapeutic adherence in uncontrolled or severe asthma.Keywords: uncontrolled asthma, severe asthma, adherence, quality of life, narrative medicine